ANALISIS PELAYANAN PRIMA ATAS KEPUASAN KONSUMEN PADA APOTEK K24 BAMBU APUS JAKARTA TIMUR - Dahlia Sarkawi; Anggi Oktaviani; Agus Priadi; Thany Khansa (Sekolah Tinggi Teknik - PLN, 2018)
Excellent service isn’t a new term in the world of work. The company must be able to give the best service to consumers so as to give satisfaction to consumers. Consumer satisfaction serve as the main key in maintaining the existence of a company. The research aims to determine the influence of excellent service to consumer satisfaction. This research use quantitative method. This research use quantitative method with 90 samples research with nonprobability sampling technique, especially purposive method. Based on data analysis, the result of research on the correlation coefficient show that 0.183 indicating that there is a very weak relationship between excellent service to consumer satisfaction. From the determination coefficient test obtained the influence of service excellent variable on cosumer satisfaction variable is 3.4% and the remaining 96.6% influenced by other variables not examined by the author. The result of simple regression obtained Y = 27,072 + 0,168X which result if excellent service is considered constant then consumer satisfaction will be positive and significant. And T test results, excellent service influence on customer satisfaction with t count > t table = 1.750> 1.662, then Ha accepted.